Exploring the potential benefits of Ethanol Direct Injection (EDI) timing and pressure on particulate emission characteristics in a Dual-Fuel Spark Ignition (DFSI) engine. (10th July 2022) - Li, Xiang; Li, Dayou; Liu, Jingyin; Ajmal, Tahmina; Aitouche, Abdel; Mobasheri, Raouf; Rybdylova, Oyuna; Pei, Yiqiang; Peng, Zhijun
Abstract: Nowadays, particulate matter emitted by vehicles severely impacts environmental quality and human health. In this paper, the potential benefits of Ethanol Direct Injection (EDI) timing and pressure on particulate emission characteristics in a Dual-Fuel Spark Ignition (DFSI) engine were initially and systematically explored. The experimental results illustrate that by delaying EDI timing from −340 °CA to −300 °CA, there is a significant benefit in both particulate number and mass concentration. Furthermore, the size distribution curve of particulate number changes from bimodal to unimodal, meantime size distribution curves of particulate mass consistently concentrate on the accumulation mode. By increasing EDI pressure from 5.5 MPa to 18 MPa, the droplet size of ethanol spray can be effectively reduced. The benefit of increasing EDI pressure is more apparent in reducing particulate number is than particulate mass. The concentration of number and mass for total particulates have a reduction of 51.15% and 22.64%, respectively. In summary, it was demonstrated that an appropriate EDI timing or high EDI pressure could be a practical and efficient way to reduce particulate emissions in a DFSI engine.